FUNCTIONAL OUTCOMES FOLLOWING LOWER EXTREMITY AMPUTATION AT THE ARMED FORCES INSTITUTE OF REHABILITATION MEDICINE USING LOWER EXTREMITY FUNCTIONL SCALE: Lower Extremity Amputation - Mansoor, Maj Sahibzada Nasir; ., Sarah Razzaq; Rathore, Farooq Azam; ., Noreen Akhtar; ., Rehana Yasmeen (Pakistan Armed Forces Medical Journal, 2013)
Objective: To assess improvement in functional outcomes following prosthetic fitting after lower limb amputation using a lower extremity functional scale in a cohort of the Pakistani population. Study Design: Quasi experimental Study. Place and Duration of Study: Amputee rehabilitation ward (indoor) / OPD (out patient department) at Armed Forces Institute of Rehabilitation Medicine Rawalpindi. From August 2009 to August 2010. Patients and Methods: Study was carried out in the amputee rehabilitation ward of the Armed Forces Institute of Rehabilitation Medicine, Rawalpindi, Pakistan. Fifty two consenting lower limb amputees fulfilling the inclusion criteria were enrolled. All patients were provided with modular prosthesis followed by gait training and integrated amputee rehabilitation program. An assessment was done at 0, 4 and 12 weeks after the provision of prosthesis. Results were analyzed by SPSS Version 15. Results: Most of the patients were males (98.1%). Mean age was 30.17±9 years . Trauma was the main etiology (99%) followed by tumor (in only 1 patient who had osteosarcoma). Transtibial amputation level was the commonest (53.8%) followed by transfemoral in 32.7% patients and Syme’s (7.7%). Lower extremity functional scale (LEFS) mean score in the first week was 35.56 (44.5% of maximum function), which improved to 49.40 (61.8% of maximum function) at week 4, and 59.27 (74.09% of maximum function) at the end of week 12. The p-value for each was 0.000. Conclusion: Early and multidisciplinary amputee rehabilitation improves the functional ambulation level, quality of life and satisfaction level of the individual.